Implementasi Penerapan Pidana Bersyarat dalam Kitab Undang-Undang Hukum Pidana (KUHP) - Herlin Hastuti (Inovasi Pratama Internasional. Ltd, 2023)
Conditional punishments regulated in the Criminal Code do not provide protection to perpetrators of criminal acts because they are not a type of crime but a way of carrying out a crime. Therefore, the Draft Criminal Code regulates criminal supervision as a new type of criminal sanction in the main crime. Supervision punishment is a substitute for conditional punishment and an alternative to imprisonment. This article examines the implementation of conditional criminal and criminal supervision arrangements in the Criminal Code Bill by looking at the implementation of criminal supervision in several countries, so that restorative justice can be realized. The criminal supervision arrangement in the Criminal Code Bill resembles the probation system in the UK, but emphasizes recovering losses incurred from criminal acts. As for the problems in writing this thesis, namely 1. How is the regulation of conditional criminal penalties in the Indonesian legislation, 2. How is the implementation of conditional crimes in Indonesia and How is the conditional criminal arrangement in the draft of the new Criminal Code. The research method can be interpreted as an important means to find, develop and test the truth of a knowledge. Therefore, before conducting research, the author first determines the method that will be used by the author. Methods or methodologies are elements that absolutely must exist in scientific research and development. Legal research is a process to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues faced. If a conditional sentence has been imposed, the supervisory officers, especially the Prosecutor, should have frequent communication with the Supervisory Judge and the Observer Judge to monitor the condition and progress of the convict. In addition, the judge also saw the events behind the criminal act as a whole as well as the attitudes and actions of the defendant in his daily life in society. It is necessary to develop and explain the science of law in the community, in order to create a society that is aware of the law.